Measurement of 129I in an Inorganic Adsorbent - Choi, K.C.; Song, B.C.; Ahn, J.H.; Park, Y.J.; Song, K.S. (Asian Journal of Chemistry, 2013)
A separation and recovery method for 129I in an inorganic adsorbent (Ag129I-zeolite) was used as a trapping filter to remove fission products and nuclear fission-generated gas. 129I was added to the AgX-exchanged zeolite and the radioactivity of the Ag129I-zeolite was determined as a reference substance for 129I. The recovery rate for 129I after alkali fusion was 76.3 ± 2.8 %. To investigate the influence of 129I in the 99Tc (Re)-containing inorganic adsorbent on separation and quantification, the recovery rate for 129I was measured after adding Re to the adsorbent. Furthermore, the recovery rate for 129I was evaluated to identify the influence of 14C in the eluted solution on 129I measurement. The results show that separation and quantification of 129I was not influenced by 14C in the eluted solution.